GEOLOGY AND RESERVOIR MODELLING OF BERKAH FIELD, A AND B INTERVAL, CENTRAL SUMATRA BASIN. - Karuna Irawan, Billy
Berkah Field is one of oil and gas field which is administratively located in Riau Province and geologically in Central Sumatra Basin with 40 km2 area. This field is located in Kiri Sub-Basin (Trough) which has normal fault trending north-south. Menggala and Upper Red Bed Formation are reservoirs in Berkah Field. Hydrocarbon-bearing intervals which are the object of this research are reservoir A and B of Menggala Formation. Goals of this research are to comprehend geological condition of research field, to determine reservoir characteristics as well as depositional facies, property, and reservoir distribution, and to estimate hydrocarbon prospect of reservoir A and B. Data used in this study consist of 3D seismic, side wall core and cutting description, biostratigraphy report, six wireline logs, and flowing test data. The result of side wall core analysis shows that there are four sandstone lithofacies (Sct, Svftm, Sg, dan Sk) dan a claystone lithofacies (Mr). The depositional environment is braided river to low-sinuousity river trending north-south with channel and floodplain facies associations. Facies modelling work is based on object modelling deterministic method. Petrophysical calculation result shows that average reservoir effective porosity is about 14- 16%. Petrophysical property modelling uses stochastic method with conditioning to facies. Volumetric calculation result of reservoir A is 1,7 million STB and reservoir B is 0,4 million STB.